Assessment of mitochondrial function and its prognostic role in sepsis: a literature review - Wagner Nedel; Nathan Ryzewski Strogulski; Afonso Kopczynski; Luis Valmor Portela (Intensive Care Medicine Experimental)
Abstract Sepsis is characterized by a dysregulated and excessive systemic inflammatory response to infection, associated with vascular and metabolic abnormalities that ultimately lead to organ dysfunction. In immune cells, both non-oxidative and oxidative metabolic rates are closely linked to inflammatory responses. Mitochondria play a central role in supporting these cellular processes by utilizing metabolic substrates and synthesizing ATP through oxygen consumption. To meet fluctuating cellular demands, mitochondria must exhibit adaptive plasticity underlying bioenergetic capacity, biogenesis, fusion, and fission. Given their role as a hub for various cellular functions, mitochondrial alterations induced by sepsis may hold significant pathophysiological implications and impact on clinical outcomes. In patients, mitochondrial DNA concentration, protein expression levels, and bioenergetic profiles can be accessed via tissue biopsies or isolated peripheral blood cells. Clinically, monocytes and lymphocytes serve as promising matrices for evaluating mitochondrial function. These mononuclear cells are highly oxidative, mitochondria-rich, routinely monitored in blood, easy to collect and process, and show a clinical association with immune status. Hence, mitochondrial assessments in immune cells could serve as biomarkers for clinical recovery, immunometabolic status, and responsiveness to oxygen and vasopressor therapies in sepsis. These characteristics underscore mitochondrial parameters in both tissues and immune cells as practical tools for exploring underlying mechanisms and monitoring septic patients in intensive care settings. In this article, we examine pathophysiological aspects, key methods for measuring mitochondrial function, and prominent studies in this field.